Three‐dimensional movements of harbour seals in a tidally energetic channel: Application of a novel sonar tracking system. Issue 4 (18th March 2019) - Hastie, Gordon D.; Bivins, Matt; Coram, Alex; Gordon, Jonathan; Jepp, Pauline; MacAulay, Jamie; Sparling, Carol; Gillespie, Douglas
Abstract: Understanding how marine predators utilize habitats requires that we consider their behaviour in three dimensions. Recent research has shown that marine mammals often make use of tidally energetic locations for foraging, yet data are generally limited to observations of animals at the water surface. Such areas are also of interest to the renewable energy industry for the deployment of tidal‐stream energy turbines; this has led to concerns about potential impacts on marine mammals. Methods for measuring animal movements underwater are limited; however, active sonar can image marine mammals and could potentially measure three‐dimensional movements in tidally energetic locations. Here, a dual 720 kHz sonar system was developed to investigate the three‐dimensional movements of harbour seals ( Phoca vitulina ) in a tidally energetic channel. Estimated mean depth (distance from the surface) of seals was 12.0 m (95% confidence intervals [CIs]: 11.6–12.4 m), and the majority of time was spent at the surface and at approximately 10–12 m distance from the surface. When expressed as distances from the sea bed, mean distance was 18.5 m (95% CI: 18.0–18.9 m), and the majority of time was spent at 14 m from the sea bed. Seal movements were generally in the same direction as the tidal flow with mean horizontal speeds of between 0.51 and 3.13 m s −1 (95% CIs = 1.24–1.54 m s −1 ). Mean vertical velocities (where negative and positive values represent a descent and ascent respectively) for each seal track ranged between −1.76 and +0.88 m s −1 (95% CIs: −0.23 to +0.03 m s −1 ). These results provide a basis for understanding how seals utilize a dynamic tidal environment and suggest that harbour seal behaviour can be markedly different to less tidally energetic habitats. The results also have important implications for the prediction of risk associated with interactions between diving seals and tidal turbines in these dynamic habitats.